FireEye: Cybersecurity in action - Singapore Management University (Institutional Knowledge at Singapore Management University, 2021)
FireEye built its success on its ‘Human + AI’ philosophy. But can a cybersecurity firm get ahead of the attackers and predict an attack…on itself?